Pengaruh Penggunaan Artificial Inteligence (AI) dalam Pembelajaran Interaktif untuk Meningkatkan Literasi Numerasi Mahasiswa - Sape, Herwandi; Muh. Ridwan; Muhammad Fuad (Almeera Education, 2025)
This study aims to analyze the effect of using Artificial Intelligence (AI) in interactive learning on improving students' numeracy literacy. The research method used is a mixed method with quantitative and qualitative approaches. Quantitative data were obtained through numeracy literacy tests before and after the application of AI, while qualitative data were collected through observations and interviews. The results showed a significant increase in students' numeracy literacy scores after using AI, with normalized gain values indicating high effectiveness. In addition, observations and interviews revealed that students were more active, independent, and engaged in AI-based learning, despite obstacles such as limited access to technology and the need for additional guidance from lecturers. In conclusion, AI contributes positively to improving students' numeracy literacy, but optimizing its application requires adequate infrastructure support and combination with conventional learning methods. This research provides implications for the development of AI-based educational technology in higher education.